Tanggung Jawab Bank Syariah dalam Penerapan Prinsip Kehati-hatian dan Good Corporate Governance - Renny Supriyatni (Universitas Islam Negeri Jakarta, 2012)
Abstract: The Responsibilities of Shariah Banking in the application of Prudential Principles and Good Corporate Governance. A Bank’s functions as an intermediary institution is interesting in relation to the importance of responsibilities to customers in applying the principles of Good Corporate Governance (GCG). The application of the principle of prudence and good corporate governance in shariah banking is useful in minimizing risks that may arise from moral hazards and avoid transactions in money laundering. The responsibility of shariah banks in the distribution of Islamic finance is basically just a little different from its application in commercial banks, caused by differences between systems that are applied by conventional banks with a shariah system which directly impact on the rules used and structures of shariah banks.Keywords: Shariah banks, principle of prudence, good governance, principles of shariahAbstrak: Tanggung Jawab Bank Syariah dalam Penerapan Prinsip Kehati-hatian dan Good Corporate Governance. Fungsi bank sebagai lembaga intermediasi menarik dalam kaitannya dengan pentingnya tanggung jawab bagi pihak nasabah dengan menerapkan prinsip Good Corporate Governance (GCG). Penerapan prinsip kehati-hatian dan Good Corporate Governance dalam Pembiayaan syariah berguna untuk meminimalisasi risiko yang mungkin timbul dari moral hazard dan menghindari transaksi yang bersifat money laundering. Tanggung jawab bank syariah dalam penyaluran pembiayaan syariah pada dasarnya hanya sedikit berbeda dengan penerapannya pada bank umum, dikarenakan adanya perbedaan antara sistem yang diterapkan oleh bank konvensional dengan sistem syariah yang secara langsung berdampak kepada aturan yang dipakai dan struktur dari bank syariah.Kata Kunci: bank syariah, prinsip kehati-hatian, tata kelola yang baik, prinsip syariahDOI: 10.15408/ajis.v12i1.985